Craniocervical necrotizing fasciitis with hepatitis and diabetes mellitus - Chen, Shan; Chen, M.D Leihui; Feng, Chongjin (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Craniocervical necrotizing fasciitis is an uncommon but aggressive infection with high mortality. The aim of this article is to review a case of severe and extensive craniocervical necrotizing fasciitis (CCNF) worsened by hepatitis and diabetes mellitus in a 32-year-old man, with a successful outcome involving early diagnosis by CT scan, broad-spectrum antibiotics, multidisciplinary treatment, multiple surgical debridement, essential intensive medical care and efficient emergency services.